Institutional Factors in the Economic growth of Mexico - Luisa Decuir-Viruez (European Regional Science Association (ERSA), 2003)
During the last three decades Mexico has grown with an annual average rate of 4%, even with the changes from an inward-looking developing economic strategy towards a more open economy with a far-reaching trade liberalisation program. But the story at the sub-national level is different; these changes have modified the regional development strategies and consequently the growth paths of the 32 Mexican states. There is evidence of an uneven growth, greater disparities and important differences in welfare standards among regions. Labour, physical and human capital are traditional factors that can explain these differences, but how much agglomeration economies and institutions have contributed to them. Using elements from the neoclassical, new growth theories and new economic geography we measure the contribution of these factors. We open the discussion on how institutional factor determine growth rate, how we define and measure them in a developing economies such as Mexico. Firstly, we assume that markets are socially constructed and economic behaviour is created in networks of interpersonal relations. Institutions are according to North(1991) the game rules, in other words, the man-designed limits that determine the forms of social relationships. The importance of these institutional elements in the regional level could be found in the contribution they have had in the reorganization of the production forms, through the reduction of transaction and production costs, the definition of the incentives structure and the changes of social participation. In this scheme, two groups of institutional elements could be identified: a)the soft institutional factors that refers to individual habits, routines, customs, traditions, social norms and values, which show some of the characteristics of the networks of interpersonal relations; b)the hard institutional factors are the long-lasting collective forces that shape the economy, such as rules, laws, constitutions, property rights, etc. However institutional factor can not explain by itself high growth rate, but added to economic and social variables, it might contribute to create a dynamic processes with higher levels of growth. Assuming this perspective, we hypothesise that the uneven regional growth in Mexico can be explained by institutional factors. Firstly, we propose that states with an economic local policy more open to trade and foreign investment have led to higher growth rates; contrasting with those states that maintain stronger links with central government. Secondly, we add some of the characteristics of the networks in the regions, in order to show if a greater participation of population and changes in the political local governments have had an impact on growth. Our results indicate that there has not been any regional convergence after the openness period (1985-2000) and that the institutional structure has a significant relation with higher growth rates states.
Keywords: 330